Chitosan/Lignin biopolymer doped samarium for potential use in drug delivery - Quezada Correa, Gilda Cecibel (2024)
Polymeric nanoparticle-based drug carriers represent a wonderful avenue for cancer therapy. In this work, we study the use of chitosan and lignin doped with Sm nanoparticles to create polymeric systems with the aim of studying their potential use as carriers of the anticancer drug, curcumin. Sm nanoparticles were synthesized by hydrothermal and precipitation methods, and characterized by XRD and TEM to observe their rod-shaped morphology. Electrostatic coassembly facilitated the formation of Chi/Lig core–shell particles, which was confirmed by SEM and EDX analysis. FTIR characterization suggested interactions between chitosan, lignin, and Sm, indicating possible hydrogen bonding and coordinate bond formation. UV-Vis spectroscopy and fluorescence microscopy confirmed the presence of Sm NPs and revealed a higher intensity at 50 ppm. Finally, we studied the encapsulation and release of curcumin in five polymeric systems: Lig-Cur, Chi/Lig-Cur, Chi/Lig/Sm-Cur, Chi-Cur, and Chi/Sm-Cur. Drug release using the polymeric systems was followed by UV-Vis spectroscopy for 28 hours, in both simulated gastric fluid (pH 3) and simulated intestinal fluid (pH 7). The presence of lignin in the polymeric systems contributed to a slower release of curcumin (less than 49%) compared to systems with pure chitosan (more than 67%), which is a favorable characteristic for their application as pH-sensitive drug carriers.